A retrospective case report on demographic changes of learners at a school for children with Autism Spectrum Disorders in Gauteng Province - Kritzinger, Alta M. (Aletta Margaretha) (University of Pretoria, 2015)
Dissertation (MComm Path)--University of Pretoria, 2015.